Konsumerisme dalam Kehidupan Masyarakat Modern: Kajian Kritis Perspektif Jean Baudrillard - Aisa Rosa; Rienika Putri; Vieronica Varbi Sununiati; Istiqomah Istiqomah; Deni Aries Kurniawan (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
Consumerism is an increasingly dominant phenomenon in modern society along with the development of capitalism, globalization, and information technology. Society's consumption patterns have shifted from being primarily oriented toward fulfilling needs to fulfilling symbolic desires. In this context, Jean Baudrillard's thinking is relevant in explaining that consumption is no longer based on use value, but rather on the sign value inherent in a commodity. This study aims to analyze the phenomenon of consumerism in modern society through Jean Baudrillard's critical perspective and to uncover its social implications. The research method used is a qualitative approach with library research, which examines various scientific literature, books, and journals related to consumerism and simulation theory. The results show that consumerism has created a pseudo-reality (simulacra), where individuals consume based on symbolic impulses shaped by the media, advertising, and popular culture. Consumption becomes a means to construct self-identity and gain social recognition, thus encouraging excessive consumer behavior. Furthermore, this phenomenon also results in social alienation, identity crises, and dependence on the global capitalist system. Thus, consumerism is not only an economic activity but also a complex socio-cultural phenomenon. Therefore, critical awareness is needed so that society can be more rational and selective in its consumption practices